2019
DOI: 10.1002/ange.201912785
|View full text |Cite
|
Sign up to set email alerts
|

A Supported Nickel Catalyst Stabilized by a Surface Digging Effect for Efficient Methane Oxidation

Abstract: A surface digging effect of supported Ni NPs on an amorphous N‐doped carbon is described, during which the surface‐loaded Ni NPs would etch and sink into the underneath carbon support to prevent sintering. This process is driven by the strong coordination interaction between the surface Ni atoms and N‐rich defects. In the aim of activation of C−H bonds for methane oxidation, those sinking Ni NPs could be further transformed into thermodynamically stable and active metal‐defect sites within the as‐generated sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Additionally, the N K-edge XANES spectrum of HCNB@G-280 displays two well defined peaks at 398.0 and 407.4 eV which are due to the excitation of the N 1 C 2 and N 1 C 1 species, respectively. [31,72] However, the HCNB@G-700 spectrum shows a new peak at 401.4 eV which corresponds to the N 1 C 3 species, and a lower intensity peak for the N 1 C 2 species, while the peak for the N 1 C 1 species remains improved, confirming the nitrogen Figure 3. a) XPS survey spectra of RGO-700, PAN, HCNB@G-280, and HCNB@G-700, b) C 1s XPS spectra of RGO-700, PAN and HCNB@G-700, c) N 1s XPS spectra of RGO-700, PAN, HCNB@G-280, and HCNB@G-700, d) the distribution of nitrogen species in all HCNB@G catalysts along with PAN for comparison; insets: the corresponding magnified C 1s spectra ranging from 293 to 287 eV.…”
Section: Bonding Feature Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, the N K-edge XANES spectrum of HCNB@G-280 displays two well defined peaks at 398.0 and 407.4 eV which are due to the excitation of the N 1 C 2 and N 1 C 1 species, respectively. [31,72] However, the HCNB@G-700 spectrum shows a new peak at 401.4 eV which corresponds to the N 1 C 3 species, and a lower intensity peak for the N 1 C 2 species, while the peak for the N 1 C 1 species remains improved, confirming the nitrogen Figure 3. a) XPS survey spectra of RGO-700, PAN, HCNB@G-280, and HCNB@G-700, b) C 1s XPS spectra of RGO-700, PAN and HCNB@G-700, c) N 1s XPS spectra of RGO-700, PAN, HCNB@G-280, and HCNB@G-700, d) the distribution of nitrogen species in all HCNB@G catalysts along with PAN for comparison; insets: the corresponding magnified C 1s spectra ranging from 293 to 287 eV.…”
Section: Bonding Feature Analysismentioning
confidence: 84%
“…As shown in Figure 4a, the RGO-700 displays a prominent peak at 284.2 eV that is attributed to the sp 2 -CC, while tiny little peaks at 287.2 and 293.1 eV can be assigned to the CO (in the conjugated ring) and to defect oriented sp 3 -CC, respectively, [70,71] these results indicate better graphitic domain restoration in graphene sheets due to the thermal treatment. However, the HCNB@G-280 sample has a new peak at 286.1 eV, which can be assigned to the CN bond, [71,72] alongside the other characteristic peaks of RGO-700. The peaks at 286.1 and 293.1 eV are much improved in the HCNB@G-700 sample, indicating the degree of the CN bonds and defective sp 3 -C have increased in the HCNB@G-700 sample.…”
Section: Bonding Feature Analysismentioning
confidence: 99%
“…11(f)). It showed that the existence of Ni single atom could improve the catalytic performance, but its loading was too high or too low will bring adverse effects on the catalysis [87]. The combination of single-atom promoter and TiO2 was closely related to the synthesis temperature.…”
Section: Molten Salt Methodsmentioning
confidence: 99%
“…In the conversion process, the nanoparticles loaded on the carrier were gradually lost during the heating process, and finally formed single atoms in situ. For example, Zhou et al [87] 6(b), carbon nanotubes (CNT@PDA for short) firstly were coated with N-containing polymer (polydopamine), and Ni nanoparticles were anchored on CNT@PDA. Subsequent to carbonization treatment under N2 protection and 600 °C for one hour, the PDA layer was transformed into an amorphous N-rich carbon layer (CNT@NC for short).…”
Section: Nanoparticles Become Single Atomsmentioning
confidence: 99%
“…Besides the widely reported application in these fields described above, SACs have also attracted intensive research interest in both experimental investigations and theoretical calculations, [ 222–225 ] such as water–gas shift (WGS) reaction, [ 210–212,226–228 ] CO oxidation, [ 34,229–231 ] methane conversion, etc. [ 232–235 ]…”
Section: Applications Of Single‐atom Catalystsmentioning
confidence: 99%